Incorporating visual methods in longitudinal transformative service research. Issue 4 (30th January 2018) - Dodds, Sarah; Bulmer, Sandy; Murphy, Andrew
Abstract : Purpose: Consumer experiences of healthcare services are challenging for researchers to study because of the complex, intangible and temporal nature of service provision. The purpose of this paper is to introduce a novel longitudinal three-phase research protocol, which combines iterative interviewing with visual techniques. This approach is utilised to study consumer service experiences, dimensions of consumer value and consumer value co-creation in a transformational service setting: complementary and alternative medicine healthcare. Design/methodology/approach: This research employed a three-phase qualitative longitudinal research protocol, which incorporated: an initial in-depth interview, implementation of the visual elicitation technique Zaltman Metaphor Elicitation Technique and a final interview to gain participant feedback on the analysis of data collected in the first two phases. Findings: Four key benefits derived from using the three-phase protocol are reported: confirmation and elaboration of consumer value themes, emergence of underreported themes, evidence of transformation and refinement of themes, ensuring dependability of data and subsequent theory development. Originality/value: The study provides evidence that a longitudinal multi-method approach using in-depth interviews and visual methods is a powerful tool that service researchers should consider, particularly for transformative service research settings with sensitive contexts, such as healthcare, and when studying difficult to articulate concepts, such as consumer value and value co-creation.